Hot off the press. Issue 12 (27th October 2016) - Hill, Robert A.; Sutherland, Andrew
Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as kanamienamide from the marine cyanobacterium Moorea bouillonii . Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as kanamienamide from the marine cyanobacterium Moorea bouillonii .